Sistem Monitoring dan Pakan Otomatis pada Ikan Lele Berbasis Mikrokontroler ESP32 - Alif Bartus Ikhrom; Rini Puji Astutik (Pusat riset dan Inovasi Nasional, 2026)
Catfish farming is one of the fisheries areas with great potential in Indonesia. However, the problem of feed efficiency, use of probiotics, and air temperature control are still the main obstacles that affect the health and growth of fish. This study aims to design and implement an automatic system that can regulate the provision of feed and probiotics and control and control air temperature directly using the ESP32 microcontroller. This system has several important components, such as the ESP32 microcontroller as a control center, servo motors for feed and probiotic distribution, and DS18B20 temperature sensors to monitor air temperature. All components can be controlled and viewed through an IoT-based application with a Wi-Fi connection or applications such as Telegram. This trial aims to determine whether this system can provide feed and probiotics according to the specified time, and maintain air temperature in the optimal range (28°C–40°C) for catfish growth. In this way, the system is expected to increase efficiency in catfish farming automatically, reduce the need for human labor, and minimize errors in pond management.